2019
DOI: 10.1108/bfj-06-2019-0465
|View full text |Cite
|
Sign up to set email alerts
|

Regional difference analyzing and prediction model building for Chinese wine consumers’ sensory preference

Abstract: Purpose The purpose of this paper is to provide further insight into Chinese wine consumers’ preference, grasp the regional sensory preference differences of China and build up a predictive model for wine consumers’ sensory preferences. Design/methodology/approach The study involved 3,421 Chinese wine consumers in the survey. Classified statistics were conducted to excavate regional differences of wine consumers’ sensory preferences. By analyzing influencing factors, prediction models for consumers’ sensory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…The literature (Chu et al, 2020) uses a predicting method based on multivariate disorder logistic and shows that this method is only suitable for predicting colour, sweetness, aroma type and taste preference with an accuracy of between 70 and 75%, whereas the wine recommendation algorithm proposed in this study achieved an accuracy of over 79% for these attributes, which is better than the method proposed in the literature.…”
Section: Construction and Verification Of Single Recommendation Modelmentioning
confidence: 78%
See 1 more Smart Citation
“…The literature (Chu et al, 2020) uses a predicting method based on multivariate disorder logistic and shows that this method is only suitable for predicting colour, sweetness, aroma type and taste preference with an accuracy of between 70 and 75%, whereas the wine recommendation algorithm proposed in this study achieved an accuracy of over 79% for these attributes, which is better than the method proposed in the literature.…”
Section: Construction and Verification Of Single Recommendation Modelmentioning
confidence: 78%
“…For example, by using a simple best-worst method, Stanco et al (2020) concluded that traditional attributes such as 'geographical indications' and 'grape variety, ' influence consumer purchase behaviour more than untraditional attributes such as 'alcohol-free wine' and 'vegan wine. ' Chu et al (2020) built a predictive model for Chinese wine consumers' sensory preferences based on multivariate disorder logistic regression method. On the other hand, using simple logistic regression algorithm is one-sided in analysing the influence of consumers' personal characteristics on wine selection.…”
Section: Introductionmentioning
confidence: 99%
“…Results highlight that wine with a red-brick color, complex smell and aggressive mouthfeel consistent with those from cooler regions was less liked by the panel than a warm climate goldawarded wine Wang and Spence (2018) Focus on the extrinsic surface texture of wine and its influence on consumer perception Findings show that surface texture (in this case velvet vs sandpaper) affects in-mouth flavor experience as well as orthonasal olfactory evaluations. It is evident the crossmodal effect between touch and smell Wang and Spence (2019) Focus on experts and the influence of wine color on aroma and flavor A total of 168 participants tasted three kinds of wine: white, ros e and a dyed fake ros e. In terms of aroma and flavor, the dyed fake ros e was similar to ros e wine, fruit descriptors were used to describe ros e and fake ros e. Mimicking the color of a ros e wine can influence the perceived aroma and flavor of a white wine Chu et al (2019) Focus on sensorial preferences of Chinese wine consumers Totally, 3,421 Chinese wine consumers were involved in a survey which showed that they preferred these attributes for wine: dry red, refreshing and soft taste, still type, moderate aroma degree and mellow aroma (continued ) It is evident that the most represented sense is sight, probably because visual cues are very powerful and immediate, and furthermore, have a deep emotional response (Hulten, 2013) (see Figure 2).…”
Section: Synthesis Of the Resultsmentioning
confidence: 99%
“…Wine odours, furthermore, are influenced by glass shape (Hummel et al, 2003) As confirmed by Spence ( 2019) crossmodal research exploded during the last years and WINE MARKETERS pay more and more attention to SENSORY MARKETING. Multisensory influence on wine is also fundamental to study international wine marketing strategies (e.g., Chu et al, 2019 focused on Chinese consumers showing their sensory preferences about wine: dry, red and with a refreshing and soft taste).…”
Section: Visual Odour and Taste Stimulimentioning
confidence: 99%
See 1 more Smart Citation